2013
DOI: 10.1016/j.jpeds.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Control Predicts 2-Year Change in Lipid Profile in Youth with Type 1 Diabetes

Abstract: Objective To test the hypothesis that a change in A1c over a follow-up interval of approximately 2 years would be associated with concomitant changes in fasting lipids in individuals with type 1 diabetes (T1D). Study design All subjects with T1D diagnosed 2002–2005 in the SEARCH for Diabetes in Youth study with at least two study visits approximately 12 and 24-months after an initial visit were included (age at initial visit=10.6±4.1 years, 48% female, diabetes duration=10±7 months, 76% non-Hispanic White, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 30 publications
4
54
5
Order By: Relevance
“…The association of HbA 1c and BMI change with lipids was positive but may be insufficient to achieve lipid goals on the basis of observational data from the SEARCH study in T1DM youth, 206 similar to the TODAY data in T2DM youth. 210 Although statins are considered safe and well tolerated in adults, long-term safety studies that follow up children into adulthood are lacking.…”
Section: Treatmentmentioning
confidence: 54%
See 2 more Smart Citations
“…The association of HbA 1c and BMI change with lipids was positive but may be insufficient to achieve lipid goals on the basis of observational data from the SEARCH study in T1DM youth, 206 similar to the TODAY data in T2DM youth. 210 Although statins are considered safe and well tolerated in adults, long-term safety studies that follow up children into adulthood are lacking.…”
Section: Treatmentmentioning
confidence: 54%
“…For T1DM, longitudinal prospective studies of at least 2 years' duration and involving between 46 and 1100 patients demonstrate that worse glucose control (increased HbA 1c ) is associated with increased LDL-c (or the highly correlated non-high-density lipoprotein [HDL] cholesterol) [202][203][204][205][206][207] and demonstrate an increase in LDL-c with increasing body mass index (BMI) or BMI z score. 203,204,206 In addition, a large crosssectional study of ≈29 000 German and Austrian patients with T1DM demonstrated strong associations between LDL-c and HbA 1c and between LDL-c and BMI. 208 From these data, it is clear that lower LDL-c levels can be achieved by improved glucose control and reduced BMI in addition to a healthy diet.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Maahs et al evaluated lipid changes during the follow-up of patients with T1D over a period of about 2 years. The authors found an association between high BMI and lipid levels independent of glycemic control and demonstrated that uncontrolled and unhealthy diets lead to increases in BMI and lipid levels and consequently to poor metabolic control [33]. Perez et al found a higher frequency of dyslipidemia among girls.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal results from a random lipid panel should be confirmed with a fasting lipid panel. Data from the SEARCH for Diabetes in Youth (SEARCH) study show that improved glucose control over a 2-year period is associated with a more favorable lipid profile; however, improved glycemic control alone will not normalize lipids in youth with type 1 diabetes and dyslipidemia (53).…”
Section: Management Of Cardiovascular Risk Factorsmentioning
confidence: 99%